2003
DOI: 10.1016/s0960-0779(03)00026-2
|View full text |Cite
|
Sign up to set email alerts
|

The golden mean as clock cycle of brain waves

Abstract: The principle of information coding by the brain seems to be based on the golden mean. For decades psychologists have claimed memory span to be the missing link between psychometric intelligence and cognition. By applying BoseEinstein-statistics to learning experiments, Pascual-Leone obtained a fit between predicted and tested span. Multiplying span by mental speed (bits processed per unit time) and using the entropy formula for bosons, we obtain the same result. If we understand span as the quantum number n o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 41 publications
3
42
0
1
Order By: Relevance
“…To model such a fractal condition in geometric terms, we prefer to postulate a nested torus modality, indicating the self-similarity and recursive elements in the framework of a scale relativity space-time theory (see for an introduction Wikipedia/Scale relativity), and further highlighted in toroidal terms in the fractalholographic universe (Bjerve, 2016). It is of interest that both the metric of brain waves (Weiss and Weiss, 2003) and the basic wave energy relations at the Planck scale have been described by golden mean ratio-like clock cycles. This aspect may also be relevant for an integral approach of brain function: Smythies (2015), described protein vibrations in information processing in the brain as a threefold nested Russian doll, while Meijer, 2014, alluded to a nested and bi-cyclic neural workspace in the concept of an extended brain function that integrates micro and macro scale imbedding of (self)-consciousness.…”
Section: Proposed Torus Model For Quantum Guided Biologymentioning
confidence: 99%
“…To model such a fractal condition in geometric terms, we prefer to postulate a nested torus modality, indicating the self-similarity and recursive elements in the framework of a scale relativity space-time theory (see for an introduction Wikipedia/Scale relativity), and further highlighted in toroidal terms in the fractalholographic universe (Bjerve, 2016). It is of interest that both the metric of brain waves (Weiss and Weiss, 2003) and the basic wave energy relations at the Planck scale have been described by golden mean ratio-like clock cycles. This aspect may also be relevant for an integral approach of brain function: Smythies (2015), described protein vibrations in information processing in the brain as a threefold nested Russian doll, while Meijer, 2014, alluded to a nested and bi-cyclic neural workspace in the concept of an extended brain function that integrates micro and macro scale imbedding of (self)-consciousness.…”
Section: Proposed Torus Model For Quantum Guided Biologymentioning
confidence: 99%
“…In order to evaluate the actual "local fractal dimensions" of goose down [16], we first need to select a representative image of down and then deal with the image to adapt the computer calculation programs.…”
Section: Methodsmentioning
confidence: 99%
“…The fractal dimension of the goose down fiber is calculated as 1.66 by computer simulations and 1.704 by actual measurement of Sandbox methods, close to the golden mean, 1.618, which assuredly reveals certain structural optimality in goose down. In the known research of the mathematical aspects, Iovane [8] showed the importance of the golden mean with respect to the large-scale structures in our universe; Weiss [16] illustrated that the principle of information coding by the brain seems to be based on the golden mean. Keshavarzi et al [17] found that the fractal dimension of turbulence is relative to 1.618; He [18] applied the golden mean to biomechanics.…”
Section: Methodsmentioning
confidence: 99%
“…The Golden Mean has a solid, if at present a sometimes coincidental and unconnected, place in: 1) the study of quantum mechanics, Coldea, et al (2010-01-07); 2) recent discoveries regarding the first excited state of the hydrogen atom, Petrusevski (2006); 3) the composition of quasi-crystals, Shechtman, et al (1984), Lifshitz (____), Shechtman (2010), Senechal (2011), Steuer (2010, Steinhardt (____); 4) the structure of DNA, Perez (1991), Yamagishi (2007), Perez (2010);5) patterns seen repeatedly in botany and the form of plants, Brousseau (1968), 6) sex selection characteristics of honeybees, Yanega (1966); 7) the study of brain waves, Weiss (2003), Roopun (2008); and 8) the gambling patterns of patrons of thoroughbred races. Cameron (2002) Following upon the above list of references to the Golden Mean one would anticipate that the Material Being Counting Machine would count a vast number of electrons and -in decreasing order -a lesser number of hydrogen atoms, quasi-crystals, strands of DNA, plants, honey bees, brains and people.…”
Section: The Materials Being Counting Machinementioning
confidence: 99%